Using ADDIE model to design an interactive booklet to introduce the clothing heritage of Asir to late childhood girls in the Muhayil Asir Governorate in the year of 1444 – 2023 - Ejeimi, Sahar Hassan; Alsheri, Aisha Hassan (Journal of Curriculum and Teaching Methodology, 2025)
This research aimed to identify the procedural steps followed in designing an interactive booklet and use it to design an interactive booklet that introduce Asir clothing heritage to late childhood girls. To achieve this, the research used applied descriptive method, and the sample consisted of two parts. The first part is related to the clothing heritage of the Asir region, and the second part is related to girls in the late childhood stage with 51 girls, aged between 9-12 years. The research also relied on the ADDIE model to create the booklet after reviewing and analyzing related studies, which helps to answer the first question of the research. For answering the second question the research followed the specific stages of the model, specifically the first three stages: analysis, design, and development. The results of the current study summarize that the "ADDIE model" is suitable for designing various educational products, that is according to the agreement of six Specialists, with percentage ranged between 66.66% and 100%, which is considered as high and acceptable percentage, Which reflects the effectiveness of its application in educational design processes. Considering this, the research recommends the innovation and design of interactive educational tools that incorporate the clothing heritage of the regions of the Kingdom, tailored to each stage of general education, to elevate the level of clothing heritage culture. It also recommends keeping up with developments in the field of e-book design to enhance educational efficiency by saving time and effort in teaching.